2011
DOI: 10.1073/pnas.1106851108
|View full text |Cite
|
Sign up to set email alerts
|

Structural basis for enabling T-cell receptor diversity within biased virus-specific CD8 + T-cell responses

Abstract: Pathogen-specific responses are characterized by preferred profiles of peptide+class I MHC (pMHCI) glycoprotein-specific T-cell receptor (TCR) Variable (V)-region use. How TCRV-region bias impacts TCRαβ heterodimer selection and resultant diversity is unclear. The D b PA 224 -specific TCR repertoire in influenza A virusinfected C57BL/6J (B6) mice exhibits a preferred TCRV-region bias toward the TRBV29 gene segment and an optimal complementarity determining region (CDR3) β-length of 6 aa. Despite these restrict… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
45
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 43 publications
(53 citation statements)
references
References 42 publications
8
45
0
Order By: Relevance
“…The strong pattern of amino acid conservation within the CDR3a region suggests that the SGGSNYKL sequence might play an important role in determining TCR specificity for D b PA 224 . This prediction is consistent with our previous work, which showed that the PA 6218 TCR used specific residues within the SGGSNYKL CDR3a sequence to make direct contacts with the PA 224 peptide and provide exquisite peptide specificity (41). To demonstrate that the biased usage of this CDR3a motif was Ag-driven and not a consequence of its prevalence in the global naive TRAV21 + repertoire, we performed CDR3a sequence analysis of TRAV21 + chains expressed by GFP + CD8 + T cells from naive PAb Rg mice and demonstrated extensive sequence diversity in this repertoire (Supplemental Table I Table I).…”
Section: Sorting Pcr and Sequencingsupporting
confidence: 80%
“…The strong pattern of amino acid conservation within the CDR3a region suggests that the SGGSNYKL sequence might play an important role in determining TCR specificity for D b PA 224 . This prediction is consistent with our previous work, which showed that the PA 6218 TCR used specific residues within the SGGSNYKL CDR3a sequence to make direct contacts with the PA 224 peptide and provide exquisite peptide specificity (41). To demonstrate that the biased usage of this CDR3a motif was Ag-driven and not a consequence of its prevalence in the global naive TRAV21 + repertoire, we performed CDR3a sequence analysis of TRAV21 + chains expressed by GFP + CD8 + T cells from naive PAb Rg mice and demonstrated extensive sequence diversity in this repertoire (Supplemental Table I Table I).…”
Section: Sorting Pcr and Sequencingsupporting
confidence: 80%
“…From a genomic standpoint, the incomplete germ-line VLRC gene serves as an equivalent of the constant gene segment, whereas the clusters of different types of donor genomic cassettes represent the functional correlates of the clusters of V, D, and J gene segments of Ig or TCR loci in jawed vertebrates (20)(21)(22). Interestingly, the donor LRRencoding cassettes are not used equally for VLR assembly, in analogy with the preferential use of certain V, D, and J segments in Ig/TCR recombinations in jawed vertebrates (23)(24)(25)(26).…”
Section: Discussionmentioning
confidence: 99%
“…This appears to be the case in our model, suggesting that this process may be modified by either TCR expansion or TCRα chain pairing. More recent reports have revealed the important contribution of the α chain in specific pMHC recognition and how TCRαβ diversity should be taken into consideration, as some specific TCR Vα pairings dictate and alter MHC restriction (48,49). In the literature, a consensus on TCR diversity of naive CD4 + Tregs was obtained, stating that more is better.…”
Section: Methodsmentioning
confidence: 99%